2009
DOI: 10.1111/j.1439-0272.1987.tb01877.x
|View full text |Cite
|
Sign up to set email alerts
|

A Possibility of Unbiased Sex Preselection in Humans by Enrichment of X or Y Chromosome Bearing Spermatozoa

Abstract: Human sex ratio is generally 1.06. The motility selected population of spermatozoa are usually Y chromosome rich. It is therefore easier to influence selected male births. Social and psychologic factors and economic needs intensified by high technology may cause further imbalance in the sex-ratio, creating a demand for techniques to influence sex selection. Such techniques may also help to handle sex linked defects.An examination of several studies on the sex chromosome distribution of human spermatozoa, based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2009
2009
2009
2009

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 14 publications
1
2
0
Order By: Relevance
“…The data presented in this study were substantiated by clinical observations showing that AIH using washed motile spermatozoa selected by the swim-up technique resulted in a sex ratio of 1.67 among 40 offsprings (Bollmann, personal communication, cited in Chaudhuri and Schill -1987). This meant a predominance of 25 male to 15 female deliveries.…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…The data presented in this study were substantiated by clinical observations showing that AIH using washed motile spermatozoa selected by the swim-up technique resulted in a sex ratio of 1.67 among 40 offsprings (Bollmann, personal communication, cited in Chaudhuri and Schill -1987). This meant a predominance of 25 male to 15 female deliveries.…”
Section: Discussionsupporting
confidence: 62%
“…monolayer Percoll method and the discon- (1988 Chaudhuri and Schill (1987) examined human spermatozoa after pretreatment of semen, based on hamster-ova-penetration (HOP) test. They observed that the selection of spermatozoa in favor of motility appears to result in an enrichment of Y bearing gametes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation